Business Responses to Climate Change Regulation in Canada and Germany: Lessons for MNCs from Emerging Economies - Eberlein, Burkard (Journal of business ethics, 2009)
This article proposes a novel mapping of the complex relationship between business ethics and regulation, by suggesting five distinct ways in which business ethics and regulation may intersect. The framework is applied to a comparative case study of business responses to climate change regulation in Canada and Germany, both signatories to the Kyoto Protocol. Both countries represent distinctly different approaches which yield significant lessons for emerging economies. We also analyze the specific role of large multinational corporations in this process.